The Right of Access to Environmental Information: From the Formality to the Effectiveness of the Rights of Access - Andressa de Oliveira Lanchotti; Jamile Bergamaschine Mata Diz (Revista de Direito e Sustentabilidade, 2016)
The Right of Access to Environmental Information is enshrined in the harvest of Human Rights as a political and civil right, essential to the guarantee of the fundamental right to a healthy and balanced environment. However, especially in the context of Risk Society, the mere declaration of such rights are not enough to ensure its effectiveness. In this sense, the present work brings an analysis of the Brazilian legislation on the subject, with the intention to understand if the national normative ensures the effectiveness of the Right of Access to Environmental Information, or if it’s made strictly in a formal way.